The complete mitochondrial genome of Leuciscus merzbacheri (Cypriniformes: Cyprinidae) - Wei Meng; Lin Li; Xiaoqian Yuan; Yongdong Zhou (Mitochondrial DNA. Part B. Resources, 2023)
Leuciscus merzbacheri (Zugmayer, 1912) is a cyprinid fish endemic to China, with a distribution range limited to Xinjiang Province. As a landmark species in the Junggar Basin, L. merzbacheri is of considerable significance regarding our understanding of the adaptive evolution of salt and alkali tolerance. In this study, the complete mitochondrial sequence of L. merzbacheri was obtained for the first time by high-throughput sequencing. The circular mitogenome is 16,609 bp in length and contains the standard 37 genes, including 13 protein-coding, 22 transfer RNA, and 2 ribosomal RNA genes, which is similar to that of other fish. The mitogenome contents of A, T, C, and G were 27.9, 26.3, 27.1, and 18.7%, respectively. Phylogenetically, L. merzbacheri was located on a new branch near the base of the phylogenetic tree, thereby suggesting an early origin.